2006
DOI: 10.1007/s00449-006-0095-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study on central metabolic fluxes of Bacillus megaterium strains in continuous culture using 13C labelled substrates

Abstract: Fluxes of central carbon metabolism [glycolysis, pentose phosphate pathway (PPP), tricarboxylic acid cycle (TCA cycle), biomass formation] were determined for several Bacillus megaterium strains (DSM319, WH320, WH323, MS941) in C- and N-limited chemostat cultures by (13)C labelling experiments. The labelling patterns of proteinogenic amino acids were analysed by GC/MS and therefrom flux ratios at important nodes within the metabolic network could be calculated. On the basis of a stoichiometric metabolic model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 23 publications
1
27
0
Order By: Relevance
“…2 and 3) revealed that the use of the ED pathway amounts to >99%, whereas glycolysis and PPP contribute only <1% (Table 2). Compared to other microorganisms such as E. coli [20], B. subtilis [21], B. megaterium [18] or C. glutamicum [22] grown on glucose, this is a rather unusual flux pattern. Most organisms use glycolysis and the pentose phosphate pathway concomitantly but at varying ratios (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…2 and 3) revealed that the use of the ED pathway amounts to >99%, whereas glycolysis and PPP contribute only <1% (Table 2). Compared to other microorganisms such as E. coli [20], B. subtilis [21], B. megaterium [18] or C. glutamicum [22] grown on glucose, this is a rather unusual flux pattern. Most organisms use glycolysis and the pentose phosphate pathway concomitantly but at varying ratios (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…The experimental set up is shown in figure 6. When metabolic steady-20 state conditions were achieved, the feed medium, containing naturally labelled glucose as carbon source, was changed to an identical medium comprising a mixture of naturally and 13 C-enriched glucose (Fürch et al 2006;Fürch et al 2007). …”
Section: Dynamic Studies Of Recombinant Protein Production In Bacillumentioning
confidence: 99%
“…Interestingly, the gluconeogenic reaction catalyzed by phosphoenolpyruvate carboxykinase was proven not to be active in all cases tested (Fürch et al 2006;Fürch et al 2007). 10…”
Section: Dynamic Studies Of Recombinant Protein Production In Bacillumentioning
confidence: 99%
“…The models have been confronted with the results from metabolome and fluxome analyses. 46,47 Consequently now, DNA microarray and proteomic experiments are the experi mental validation for the proposals. Furthermore, integration of regulatory and metabolic networks is desired.…”
Section: The Next Revolution: "Systems Biotechnology"mentioning
confidence: 99%